Effect of different composition and emulsifier types on the stability of red palm oil emulsified powder / Ghina Sovia Putri ... [et al.] - -, Ghina Sovia Putri; Saudia, Tsalitsa Nuris; Paramita, Vita; Ariyanto, Hermawan Dwi (Universiti Teknologi MARA Shah Alam, 2023)
Red palm oil (RPO) has high nutritional content such carotene and vitamin E. However, those components in RPO are unstable and sensitive when exposed to light or temperature. Thus, the sensitive and unstable of nature components of red palm oil highlights the importance of encapsulation process via emulsification in early stage. The objective of this study was to investigate the stability of β-carotene in RPO encapsulated powder using α-cyclodextrin as wall material with the comparison of the emulsifier used between sodium caseinate (NaCAS) and lecithin in terms of production of RPO encapsulated powder. The protective effects provided by encapsulated powder process were evaluated in terms of the degradation kinetics of β-carotene at 60 ℃ for 25 days. Stability of β-carotene in RPO emulsified powder was fitted well using a first kinetic model. Degradation of β-carotene in encapsulated powder could be correlated using the first kinetic model. The stability of β-carotene with lecithin as emulsifier in both solid contents (25 wt.% and 35 wt.%) were more stable with degradation rate constant 0.018 day−1 and 0.016 day−1, respectively. Encapsulation process protected RPO during storage, with lecithin emulsifier performing better than NaCAS emulsifier.